(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Starting from the fact that double standards exist in the policies and legislative acts in the European Union, as regards to food products and food distribution in the EU market, like for example in Germany and Austria food products are being placed on the market with a higher quality and more accessible prices, while in Bulgaria and Slovak Republic the same products that are being distributed are of lower quality and higher prices. The situation is similar in the field of EU’s Foreign Policy towards acceeding countries. For example the EU has granted membership to Cyprus and Croatia that still have open territorial disputes, but on the other side the EU has stalled the Eurointegrative processes for Republic of Macedonia because of its name dispute, where in spite of international documents that guarantee the right of Republic of Macedonia for membership in international organizations, the EU does not take them in consideration. In base of that, the purpose of the paper is to investigate the coherence of the Foreign policy of the European Union towards Republic of Macedonia vis-á-vis the membership of Cyprus and Croatia.